A new species of Brachycephalus (Anura: Brachycephalidae) from the Quiriri mountain range of southern Brazil - Pie, Marcio R.; Ribeiro, Luiz F. (PeerJ, 2015)
A new miniaturized toadled of the genus Brachycephalus (Anura: Brachycephalidae) is described from Serra do Quiriri in the municipality of Campo Alegre, Santa Catarina, southern Brazil. Specimens were collected from the leaf litter between from 1,263 and 1,318 m above sea level. The new species is distinguished from all its congeners by the combination of the following characters: snout–vent length 9.9–13.1 mm; skin on head and dorsum without dermal co-ossification; snout mucronate in dorsal view; dorsum rugose; general color brown, with a narrow orange vertebral stripe. The region where the new species is located is also shared with other endemic anuran species and has experienced strong anthropogenic impacts,suggesting that immediate actions should be taken to ensure their long-term preservation.
Keywords: Amphibia; Atlantic Rainforest; Cloud forest; Terrarana; Serra do Quiriri